2009
DOI: 10.1371/journal.pcbi.1000260
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Mechanical Model of T-Killer Cell Polarization Reproduces the Wandering of Aim between Simultaneously Engaged Targets

Abstract: T-killer cells of the immune system eliminate virus-infected and tumorous cells through direct cell–cell interactions. Reorientation of the killing apparatus inside the T cell to the T-cell interface with the target cell ensures specificity of the immune response. The killing apparatus can also oscillate next to the cell–cell interface. When two target cells are engaged by the T cell simultaneously, the killing apparatus can oscillate between the two interface areas. This oscillation is one of the most strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 19 publications
(49 reference statements)
6
36
0
Order By: Relevance
“…The centrosome moves to the immunological synapse by cortical pulling (Kim and Maly, 2009) and directs the delivery of lytic granules (Stinchcombe et al, 2006;Tsun et al, 2011) (Fig. 2D).…”
Section: Immune Cellsmentioning
confidence: 99%
“…The centrosome moves to the immunological synapse by cortical pulling (Kim and Maly, 2009) and directs the delivery of lytic granules (Stinchcombe et al, 2006;Tsun et al, 2011) (Fig. 2D).…”
Section: Immune Cellsmentioning
confidence: 99%
“…For certain initial conditions (which in reality are unique for each cell), the "jamming" may become spontaneously resolved through a catastrophic stability loss of the static equilibrium in the "jammed" cell. 22 on asymmetrically toward a certain, as yet undiscovered, cortical site? Such a site, while being arbitrarily oriented in the laboratory frame of reference, could nonetheless provide a directional bias for the thermodynamic tendency of the cytoskeleton toward arbitrary eccentricity.…”
Section: Mechanics Of Autonomous Asymmetrymentioning
confidence: 99%
“…14 Kim and Maly 22 simulated the bending of the microtubules and the pulling force exerted on them by dynein that accumulates on the inner surface of the interface. 23,24 Similarly to the numerical models of the Caenorhabditis elegans zygote, they found that the equilibrium does not persist, and oscillations develop spontaneously.…”
Section: Systems Biomechanics Of Centrosome Positioningmentioning
confidence: 99%
See 2 more Smart Citations